Review of Fiqh Jinayah and Criminal Law on Law Enforcement of Cockfighting Gambling - Dedi Bahar; Rusdaya Basri; Islamul Haq (DELICTUM : Jurnal Hukum Pidana Islam, 2022)
The results of this study discuss jināyah fiqh and criminal law on cockfighting gambling law enforcement (study of decision number 45/Pid.B/2016/PN Pre, the main problems in this study are, how is the analysis of the considerations against the perpetrators of cockfighting gambling in the decision number 45/Pid.B/2016/PN Pre and how is the analysis of jināyah fiqh against cockfighting gamblers in the decision number 45/Pid.B/2016/PN Pre. This type of research uses descriptive qualitative methods, including field research, using normative and juridical theological approaches, while the source of data in this study comes from primary data with the Parepare district court study and secondary data, namely data relating to documents, books, journals and others. Data collection techniques in this research are case studies, interviews and documentation. The results of this study indicate that 1). The judge in sentencing the judges if they saw some mitigating or aggravating considerations for them, so that the judges sentenced them to 3 months and 15 days in prison to be imposed. 2). In Islamic law, gambling crime or also called maysir is included as a jarīmah crime whose punishment provisions are jarīmah ta'zīr, namely the provision of punishment in the form of ta'zīr sanctions provisions depending on the punishment given by the judge or ulil amri/ruler by considering the circumstances of the objectives to have an effect. deterrent not to repeat the action.